Current trends in Packaging for agricultural products - Bayona - Boneth, Yasleidy; Palencia - Boneth, Leidy Yohana; Hoyos - Patiño, Johann Fernando; Velásquez - Carrascal, Blanca Liliana; Garcia - Quintero, Carmen Liceth (Universidad Francisco de Paula Santander, 2023)
The packaging investigates the methods of visually informing the value of a product, highlighting the excellent, efficient and important communicator between the brand and the customer. The article aims to analyze the current trends of packaging in agricultural products, highlighting the importance of packaging in the sector, in addition, it will recognize the different innovations and creative processes at present and identify the benefits for companies in the agricultural sector with the good management of packaging. For its development, the literature review method was used, it contains and analyzes a high number of bibliographic citations, in a period from 2018 to 2022, with only 5 years of provenance in order to increase the information and veracity of the article. As a result, it is inferred that most buyers are attracted by the packaging design, therefore, it is determined that packaging is currently becoming a primary tab in agricultural products.